Wavelet Coherence and Continuous Wavelet Transform - Implementation and Application to the Relationship between Exchange Rate and Oil Price for Importing and Exporting Countries - Aladwani, Jassim (International Journal of Energy Economics and Policy, 2023)
The purpose of this study is to analyses the time–frequency relationship between exchange rate and the oil price for exporting and importing countries by using measures of continuous wavelet transform (CWT) and Wavelet coherence (WCT). The findings of wavelet coherence (WCT) analysis indicates that the high coherency between exchange rates and oil price is witnessed in Brazil, Singapore, and Taiwan in medium and long term for importing countries while in Kuwait, Russia, and Canada for exporting countries. In addition, there is no co-movement between the exchange rates and oil price for Angola, Venezuela, Iraq, and Iran for exporting countries while in Egypt for importing countries in short, medium, and long term. In addition, in most of the period studied, exchange rate for importing and exporting countries was leading and passing anti-cycle effects on oil price (OPEC, BRENT, and WTI) shocks which are the major contribution of our study.